Severe hypoglycaemia under abemaciclib administration in a patient with breast cancer: A case report - Horie, Tatsuo (Mol Clin Oncol, 2021)
The current study reports the case of an 80-year-old woman who experienced severe hypoglycaemia after abemaciclib administration, with a recovery time of ~46 h. Abemaciclib is a cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitor that is used to treat metastatic breast cancer. A side effect of abemaciclib administration is an increase in creatinine levels. The half-life (t(1)(/)(2)) of 150 mg abemaciclib in patients with breast cancer was reported to be 17.5 h (nearly lower limit), and the time to reach C(max) was ~5 h (T(max), 4-6 h). Therefore, the total time to reach half the maximum blood concentration after abemaciclib administration is ~24 h (T(max) + t(1)(/)(2)=5+17.5=22.5 h). As abemaciclib is administered twice daily, a considerable amount (C(max) = 123 ng/ml) may persist in the blood following the initial dose. Upon repeated administration, the blood abemaciclib concentration in patients with metastatic liver tumours might increase, although their liver function remains normal. The patient described in the current study had a creatinine level of 1.05 mg/dl at the start of abemaciclib administration. At the time of emergency hospitalisation (on day 5 of abemaciclib administration), the creatinine level was 1.40 mg/dl; however, dehydration was not observed. The patient had been administered the same dose of glimepiride for >1 year and had not experienced hypoglycaemia previously. It can be speculated that the increase in blood creatinine level had some effect on glimepiride metabolism. It is thought that administered abemaciclib enhances metabolic delay in the blood in the same way as in patients with impaired liver function, and as a result, the creatinine level increases in patients with liver metastases. This causes a decrease in renal function, which in turn results in an increase in blood concentration of glimepiride, consequently leading to severe hypoglycaemia. Therefore, clinicians must be careful when using abemaciclib in patients with liver metastases, diabetes and poor renal function.